Significance of autoimmune disease in severe pulmonary hypertension complicating extensive pulmonary fibrosis: a prospective cohort study. (1st April 2021) - Saggar, Rajeev; Giri, Paresh C.; Deng, Chunqin; Johnson, Dana; McCloy, Mary K.; Liang, Lloyd; Shaikh, Faisal; Hong, Jason; Channick, Richard N.; Shapiro, Shelley S.; Lynch, Joseph P.; Belperio, John A.; et al.
Abstract : The association of autoimmune disease (AI) with transplant‐free survival in the setting of severe Group 3 pulmonary hypertension and extensive pulmonary fibrosis remains unclear. We report cases of severe pulmonary hypertension (mean pulmonary artery pressure ≥35 mmHg and right ventricular dysfunction) and extensive pulmonary fibrosis after pulmonary arterial hypertension‐specific therapy. We used multivariate regression to determine the clinical variables associated with transplant‐free survival. Of 286 screened patients, 55 demonstrated severe pulmonary hypertension and extensive pulmonary fibrosis and were treated with parenteral prostacyclin therapy. The (+)AI subgroup (n = 34), when compared to the (–)AI subgroup (n = 21), was more likely to be female (77% versus 19%) and younger (58.7 ± 12.1 versus 66.0 ± 10.7 years), and revealed lower forced vital capacity (absolute) (1.9 ± 0.7 versus 2.9 ± 1.1 L), higher DL CO (% predicted) (31.1 ± 15.2 versus 23.2 ± 8.0), and increased unadjusted transplant‐free survival (1 year (84.6 ± 6.3% versus 45 ± 11.1%)), 3 years (71 ± 8.2% versus 28.6 ± 11.9%), and 5 years (47.6 ± 9.6% versus 6.4 ± 8.2%); (p = 0.01)). Transplant‐free survival was unchanged after adjusting for age and gender. The pulmonary hemodynamic profiles improved after parenteral prostacyclin therapy, independent of AI status. The baseline variables associated with mortality included age at pulmonary hypertension diagnosis (heart rate (HR) 1.23 (confidence interval (CI) 1.03–1.47); p = 0.02) and presence of AI (HR 0.26 (confidence interval (CI) 0.10–0.70); p < 0.01). Gas exchange was not adversely affected by parenteral prostacyclin therapy. In the setting of severe Group 3 pulmonary hypertension and extensive pulmonary fibrosis treated with pulmonary arterial hypertension‐specific therapy, AI is independently associated with increased transplant‐free survival. Pulmonary hypertension/pulmonary fibrosis associated with AI should be considered in future clinical trials of pulmonary arterial hypertension‐specific therapy in Group 3 pulmonary hypertension.